Warning that a three degree rise in temperature will 'cancel out' european emission reduction efforts.
As a debilitating heat wave, nicknamed 'Lucifer' by the press, currently engulfs southern Europe, a new study part-supported by two EU-funded projects has warned that a rise in global temperatures of three degrees would reverse Europe's dedicated efforts to reduce ozone pollution.